Nuclear annihilation and contemporary American poetry ways of nothingness - Gery, John 1953- (Univ. Press of Florida, 1996)
The first full-length study of nuclear theory and American poetry, this book examines four distinct poetic approaches to nuclear culture - protest poetry, apocalyptic lyric poetry, psycho-historical poetry, and the poetry of uncertainty. Each is developed through a discussion of representative poems from a range of poets, including an extended study of works by Denise Levertov, Richard Wilbur, James Merrill, and John Ashbery. As a chorus of voices, Gery contends, these poets articulate both resistance to annihilation and an acceptance of the nuclear present